1984
DOI: 10.1002/tea.3660210106
|View full text |Cite
|
Sign up to set email alerts
|

Science choices and preferences of middle and secondary school students in Utah

Abstract: This research sought to answer two questions: (1) What are Utah junior and senior high school students' preferences and choices regarding science subjects? (2) Could preferences and choices be related to the type of school, age or gender? Two thousand students from grades six through twelve participated in this study. Findings show that zoology and human anatomy and physiology were most preferred. Ecology was least prefered. Topics in the physical sciences were also low. There was a trend among girls to prefer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
13
0
1

Year Published

1986
1986
2016
2016

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 9 publications
3
13
0
1
Order By: Relevance
“…They found differences favoring gifted girls in biology, but favoring gifted boys in chemistry and physics. Similar findings in the research were also found by Baird, Lazarowitz, and Allman (1984) and Kahle, Parker, Rennie, and Riley (1993). In both studies, girls reported greater interest in sciences associated with plants and animals, and boys with matter and energy.…”
Section: Science Interest Continuumsupporting
confidence: 88%
“…They found differences favoring gifted girls in biology, but favoring gifted boys in chemistry and physics. Similar findings in the research were also found by Baird, Lazarowitz, and Allman (1984) and Kahle, Parker, Rennie, and Riley (1993). In both studies, girls reported greater interest in sciences associated with plants and animals, and boys with matter and energy.…”
Section: Science Interest Continuumsupporting
confidence: 88%
“…A number of studies provide evidence that humans have higher preference, superior recall, and visual detection of animals relative to plants. Baird et al (1984) and Wandersee (1986) both surveyed secondary school students in the United States (sample sizes of 1855 and 136 students, respectively) to test preferences for science topics and found clear preference for studying zoological over botanical topics. Kinchin (1999) tested preferences of 162 students (U.K. residents) for specimens of an unfamiliar plant and animal in the classroom and found an overwhelming preference for animal over plant specimens.…”
Section: Assessing the Evidence For Plant Blindnessmentioning
confidence: 99%
“…." Studies in Science Education have shown that differences exist between boys and girls' choices and their preferences of science subjects offered at the high school level (Jungwirth, 1973;Tamir, 1975;Entwistle and Duckworth, 1977;Lazarowitz and Hertz-Lazarowitz, 1979;Baird et al, 1984). The above studies seem to indicate that while boys are more oriented toward so-called "hard" science subjects (physics, mathematics, chemistry, etc.…”
Section: Reuven Lazarowitzmentioning
confidence: 97%